2008
DOI: 10.1111/j.1365-2141.2008.07386.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding haemophilic arthropathy: an exploration of current open issues

Abstract: SummaryHaemophilic arthropathy is joint damage evolving from recurrent joint bleeds that occur in patients suffering from the clotting disorder haemophilia. Insight into the pathogenetic mechanism of this blood-induced arthropathy yields possible treatment targets and modalities useful to reduce this invalidating co-morbidity of haemophilia. Joint bleeding leads to initially independent adverse changes in both the synovial tissue and the articular cartilage. These subsequently influence each other: the synovia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 57 publications
1
115
0
4
Order By: Relevance
“…Our data suggest that the synovitis may play a crucial role in blood-induced arthropathy provoking an overreaction which subsequently becomes independent from bleeding, as postulated in other studies. 36,37 In addition, on the basis of our findings, the reduction in OPG seems to play a pivotal role in the progression of arthropathy and could even serve in the future as a biomarker of disease severity. Thus, an early clinical, instrumental and serological screening of all hemophiliacs may be recommended.…”
Section: Discussionmentioning
confidence: 71%
“…Our data suggest that the synovitis may play a crucial role in blood-induced arthropathy provoking an overreaction which subsequently becomes independent from bleeding, as postulated in other studies. 36,37 In addition, on the basis of our findings, the reduction in OPG seems to play a pivotal role in the progression of arthropathy and could even serve in the future as a biomarker of disease severity. Thus, an early clinical, instrumental and serological screening of all hemophiliacs may be recommended.…”
Section: Discussionmentioning
confidence: 71%
“…They may suffer from hemarthrosis and severe arthropathy and need regular treatment with coagulation factor concentrates. The majority of hemophilia patients treated before the introduction of viral inactivation were infected with hepatitis C and/or HIV [31][32][33]. Previous studies found that HR-QoL is mainly dependent on severity of hemophilia, age, orthopedic status, hepatitis C infection and comorbidities [34][35][36][37].…”
Section: Quality Of Life With Von Willebrand Disease 1495mentioning
confidence: 99%
“…Jansen et al [3] claimed that joint bleeding results in initially independent adverse changes in both synovial tissue and articular cartilage. These changes subsequently influence each other, with inflammatory changes in the synovium bringing about cartilage damage and vice versa.…”
Section: Pathophysiologymentioning
confidence: 98%